Animated critical theory: Nasrettin Hoca anecdotes as an animation of theories of Marx, Foucault and Simmel - Balaman, Ayşe. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
The purpose of this study at the global level is to draw attention to points of convergence in Eastern and Western sourced tendencies of pre-modern and modern/post-modern thought, while the immediate objective is to discover overlapping themes in the approach to cultural critique present in both. The study will feature, as an illustration of the former, selections of Nasrettin Hodja anecdotes which consist of very short narrations of incidents featuring the Turkish Nasrettin Hodja, a thirteenth century historical figure known as a folk philosopher with international eminence for his wise and humorous remarks concerning cultural practices. The latter will be represented by the critical and cultural theories put forward by the nineteenth century German political economist-sociologistphilosopher Karl H. Marx, twentieth century French historian-philosopher Michel Foucault, and the nineteenth and twentieth century German sociologist-philosopher Georg Simmel. Regarding the cultural critique in the anecdotes, this study will focus on the recognition of the dynamic quality of object and subject roles in a given cultural incident involving man to himself, man to man, man to animal or man to knowledge relationships. In the said theories, this dynamism is found in the form of a process of continual exchange between object and subject components, which finds a different meaning in each theory. In Marx’s theory, this idea is spelled out in terms of historical dialectic employed in the formulation of “revolutionary practical-critical activity”. With Foucault, this exchange emerges as the simultaneity of man’s object and subject roles in relation to possession of knowledge which he states to be consequential of the transfer from the classical to the modern eras of knowledge. Finally in Simmel’s writings the dynamism in object subject exchange is seen in the form of reciprocity between objective and subjective cultures, the discussion of which he employs in describing modernity and the relevant categories of social experience he analyses. This study proposes to demonstrate, through the method of content analysis, that the recognition of subject object role exchange present in a variety of forms in the abovementioned theories is depicted in practice form in the Nasrettin Hodja anecdotes, providing an animated theory. Considering the difference in the cultural origins as well as in the eras of the said approaches, discovery of this convergence in thought is meant to stimulate a rereading of the East/West and pre/post modern dichotomies.
Keywords: Critical theory.